Genetic disorders of neurotransmitter release machinery - Uzay, Burak; Kavalali, Ege T. (Frontiers in Synaptic Neuroscience, 2023)
Synaptic neurotransmitter release is an evolutionarily conserved process that mediates rapid information transfer between neurons as well as several peripheral tissues. Release of neurotransmitters are ensured by successive events such as synaptic vesicle docking and priming that prepare synaptic vesicles for rapid fusion. These events are orchestrated by interaction of different presynaptic proteins and are regulated by presynaptic calcium. Recent studies have identified various mutations in different components of neurotransmitter release machinery resulting in aberrant neurotransmitter release, which underlie a wide spectrum of psychiatric and neurological symptoms. Here, we review how these genetic alterations in different components of the core neurotransmitter release machinery affect the information transfer between neurons and how aberrant synaptic release affects nervous system function.